Hubungan Higiene Personal Terhadap Kejadian Tinea Versicolor Pada Santri Pria Di Pondok Pesantren Darussa’adah Mojo Agung, Lampung Tengah - Soni Setiya Wardana; Fitria Saftarina; Tri Umiana Soleha (Medula, 2020)
Tinea versicolor is an infection of superfisial fungal caused by Malassezia furfur, chronic, mild and usually without inflammation. Tinea versicolor occurs because of the condition that affect the balance between host and the fungal. Personal hygiene influenced by body image, social practic, social economic status, knowledge, culture, personal choices and physical condition. Poor personal hygiene levels is a risk factor for tinea versicolor. This study aimed to determine the relationship between personal hygiene and the incidence of tinea versicolor on male students in islamic boarding school. This study is an analytic observational with quantitave research method and cross-sectional approach. The sample in this study were 68 male students at the islamic boarding school. The diagnosis of tinea versicolor confirmed by clinical and microscopic findings on skin scrapings. Bivariate data analysis using chi square test (????=10%; CI=90%). The results of this study showed that 58,6% of respondents have a poor personal hygiene and 21,4% of the respondents had tinea versicolor. From chi sqaure test analysis, it was found that the relationship of personal hygiene and the incidence of tinea versicolor statistically significant with p=0,013. From this study we can conclude that there was a relationship between personal hygiene and the incidence of tinea versicolor.